2022
DOI: 10.1186/s13011-022-00437-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and pattern of cannabis use among patients attending a methadone treatment clinic in Nairobi, Kenya

Abstract: Background Cannabis use during methadone treatment may negatively impact treatment outcomes. The aim of this study was to determine the prevalence and pattern of cannabis use among patients attending a methadone treatment clinic in Nairobi, Kenya. Methods This was a retrospective study of 874 patients on methadone therapy at a methadone maintenance treatment clinic in Nairobi, Kenya from December 2014 to November 2018. Data on sociodemographic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Poverty, political instability, social unrest, and refugee issues in Africa have led to the rapid spread of psychoactive substance use, especially among young people. Low educational attainment is a risk factor for cannabis use disorder (Ngarachu et al, 2022 ; Odejide, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Poverty, political instability, social unrest, and refugee issues in Africa have led to the rapid spread of psychoactive substance use, especially among young people. Low educational attainment is a risk factor for cannabis use disorder (Ngarachu et al, 2022 ; Odejide, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show concurrent substance use is common among patients with Opioid Use Disorder (OUD) [4,[6][7][8]. The most frequent concurrent substances include alcohol, tobacco, cannabis, benzodiazepines, and amphetamines at different rates [4,[8][9][10]. A national survey on the status of substance use in Kenya showed that more than 50% of the population had ever used a substance in their lifetime [11].…”
Section: Introductionmentioning
confidence: 99%
“…With half of the estimated people who inject drugs (PWID) dwelling in the Kenyan coastal counties, Mombasa and Kilifi counties were prioritized for MMT initiation in 2015 [ 10 – 12 ]. While various studies conducted in Kenya on people with opioid use disorder mostly focused on the period prior to MMT enrolment [ 13 15 ], a few studies have enquired about its effect on polydrug use, other related risky behaviour, productivity, household income food insecurity, and the economic cost of methadone [ 12 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%